2005
DOI: 10.1007/s11259-005-1867-2
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Binding to Sorbents in Bovine Ruminal Fluid

Abstract: A recent approach to the problem of contamination of agricultural products by aflatoxin B(1) (AFB(1)) is to add non-nutritional adsorbents to animal diets in order to sequester ingested aflatoxins. We conducted in vitro experiments to develop a rapid and cheap model using ruminal fluid to assess the ability of sorbent materials to bind AFB(1). Seven sorbents (hydrated sodium calcium aluminosilicate; clinoptilolite; zeolite; two types of bentonite; sepiolite; and PHIL 75), commonly added to bovine diets were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 20 publications
1
22
0
6
Order By: Relevance
“…In addition, the studies carried out to evaluate FB1 carry-over to bovine milk are conflicting (Spotti et al, 2001a). This may be due to the lack of sensitive analytical methods for this matrix.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the studies carried out to evaluate FB1 carry-over to bovine milk are conflicting (Spotti et al, 2001a). This may be due to the lack of sensitive analytical methods for this matrix.…”
Section: Resultsmentioning
confidence: 99%
“…A few and quite dated works evaluated the presence of FB1 in milk. Some showed that fumonisins can be transferred at low concentration to bovine milk (Hammer, Blüthgen, & Walte, 1996;Maragos & Richard, 1994;Spotti et al, 2001a), while others found no milk contamination with FB1 (Richard et al, 1996;Scott, Delgado, Prelusky, Trenholm, & Miller, 1994). However, all the methods used had a LOQ between 1 and 50 lg/kg (Hammer et al, 1996;Maragos et al, 1994;Richard et al, 1996;Scarano, Grasso, Arace, Oliviero, & Serpe, 2001;Scott et al, 1994;Spotti et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Como resultado de la dilución energética de la dieta como consecuencia de la adición de zeolita, podría esperarse un ligero incremento en el consumo; sin embargo, por las propiedadesadsorbentes, que modifican la viscosidad de los fluidos, la zeolita (Spotti et al 2005) podría disminuir la tasa de pasaje lo que se traduciría en un efecto compensatorio en la regulación Tabla II. Influencia del nivel de suplementación de zeolita sobre el rendimiento productivo y utilización aparente de la energía neta de la dieta (Influence of zeolite supplementation level on growth performance and apparent dietary net energy).…”
Section: Resultados Y Discusiónunclassified
“…La clinoptilolita cálcica es la zeolita natural más abundante y debido a su gran capacidad de intercambio catiónico es ampliamente utilizada en la agricultura. Por sus características adsorbentes, que modifican la viscosidad de los fluidos (Spotti et al, 2005), y su gran afinidad para retener y liberar nitróge-no amoniacal (N-NH 3 ), las zeolitas son prometedoras como aplicación en aditivos alimenticios para rumiantes (Mumpton y Fishman, 1977) ya que estos efectos pueden favorecer la eficiencia de la fermentación ruminal y la absorción de nutrimentos, reflejándose en una mayor eficiencia en la utilización de la energía neta aparente de la dieta. Sin embargo, los efectos sobre la utilización de nutrimentos y de respuesta productiva en rumiantes suplementados con zeolitas son inconsistentes ya que en varios estudios se ha informado de respuestas positivas (Pond, 1984;Ghaemnia et al, 2010;Goodarzi y Nanekarani, 2012), mientras que en otros, no se han observado ventajas, o incluso, se informan resultados negativos cuando las zeolitas son utilizadas (Galyean y Chabot, 1981;Sherwood et al, 2005).…”
Section: Introductionunclassified
“…Its dimensional structure is characterised by the ability to lose and gain water reversibly and to exchange cations without major change of their structure (Trckova et al 2011). Because of its sorbent properties that modify ruminal fluid viscosity (Spotti et al 2005), and binding capacity with NH 3 -N, clinoptilolite may have application as a feed additive in ruminant nutrition (Mumpton and Fishman 1977). In several studies (Pond 1984, Ghaemnia et al 2010, effects of clinoptilolite supplementation resulted in positive responses on growth performance.…”
Section: Introductionmentioning
confidence: 99%